Memahami Hubungan Teori Psikoanalisis dan Teori Pengembangan Moral terhadap Terjadinya Suatu Kejahatan di Masyarakat - Febrina Hertika Rani; Dea Justicia Ardha; Heni Marlina (Universitas Batanghari Jambi, 2022)
Crime is a complex phenomenon that can be understood from different sides. Thus, it is not easy to understand the crime itself. Until now, the science of criminology has developed. In criminology, there are many theories to understand crime. In the modern era, criminology is defined as a science that studies and discusses about crime and human behavior deviations both as a social phenomenon or psychology. Therefore, the legal world requires other disciplines that are able to explain each deviation, its relation to behavior, as well as certain psychological situations that motivate criminal behavior. The problem in this research is what is the correlation between psychoanalytic theory and moral development theory on the occurrence of a crime in society? This research uses normative research. Psychoanalytic theory of criminality links delinquent and criminal behavior with a